From error to correction: Appealing Arbitral Awards in Ecuador - Maldonado Garcés , Nicolás Camilo (Revista Ecuatoriana de Arbitraje, 2025)
The challenge of arbitral awards stands at the intersection of an evolving legal environment and a growing interest in arbitration as a preferred mechanism for conflict resolution. In the Ecuadorian context, where arbitration has become a valuable tool for dispute resolution, it is crucial to understand the mechanisms and limitations associated with challenging awards. This article explores the Ecuadorian regulatory framework surrounding challenges to awards. It also includes a comparative legal analysis, examining how other legal systems address the challenge of arbitral awards. Subsequently, the article briefly discusses the implementation of optional challenges to awards within the new CIAM-CIAR regulation. This analysis considers how such mechanisms could enhance the arbitration system in Ecuador, providing a contextualized view of the role of arbitration in conflict resolution in the country.